Strategy of Media Education: Philosophical and Pedagogical Aspects - Nikolaeva, Evgeniya Mikhailovna; Kotliar, Polina Sergeevna (Journal of History Culture and Art Research, 2017)
Modern requirements for educational activities have a binary nature. Thus, on the one hand, educational practice established in the form of a social institution is one of the most conservative areas of social space. On the other hand, comfortable adaptation of a person to the processes occurring in the modern world is impossible without taking into account the phenomena of digital nature. The article provides a philosophical and pedagogical strategy aimed at the development of critical and creative thinking skills and competent reasoning, which can act as a basis for media education. The paper shows that the community of researchers is an interactive form of lesson organization, which makes it possible to develop rationality and ethical-and-democratic behaviour and, thus, to promote information and media literacy among students. The article also presents theoretical justification of the strategy, as well as techniques and materials for its empirical assessment. These can help arrange a lesson according to the principle of research community, which will contribute to the development of both cognitive and ethical-and-social skills in students.